2005
DOI: 10.1109/tit.2005.850079
|View full text |Cite
|
Sign up to set email alerts
|

Capacity-Achieving Ensembles for the Binary Erasure Channel With Bounded Complexity

Abstract: We present two sequences of ensembles of non-systematic irregular repeat-accumulate codes which asymptotically (as their block length tends to infinity) achieve capacity on the binary erasure channel (BEC) with bounded complexity per information bit. This is in contrast to all previous constructions of capacity-achieving sequences of ensembles whose complexity grows at least like the log of the inverse of the gap (in rate) to capacity. The new bounded complexity result is achieved by puncturing bits, and allow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 15 publications
2
100
0
Order By: Relevance
“…In Table I we give the thresholds for the BSC transition probability for which the error bound (7) decays to zero, for some choices of q. It is apparent that the threshold worsens as q increases.…”
Section: Discussion and Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table I we give the thresholds for the BSC transition probability for which the error bound (7) decays to zero, for some choices of q. It is apparent that the threshold worsens as q increases.…”
Section: Discussion and Numerical Resultsmentioning
confidence: 99%
“…Let ǫ > 0 be some positive number. If the transition probability p satisfies p < q −4(ǫ+1+ 1 2 log q (4q−2)) , then when decoded using the RALP decoder, the code has word error probability WEP < K(log q n) · n −ǫ (7) where K is a positive constant.…”
Section: An Error Bound For Regular Ra(q) Codes With Even Qmentioning
confidence: 99%
See 1 more Smart Citation
“…A local stopping set for this CN is a subset of the local code bits such that, if all of these bits are erased, MAP decoding cannot recover any of these bits. This occurs if and only if each column of G corresponding to erased bits is linearly independent of the columns of G corresponding to the non-erased bits 6 . The size of the local stopping set for the CN is equal to the number of erased local code bits.…”
Section: Growth Rate Of the Weight Distribution Of The Irregular Dmentioning
confidence: 99%
“…A lower-bound on the density of a parity-check matrix in terms of the multiplicativecapacity-gap ǫ was obtained in [3] and later tightened in [7]. For a code defined by a full-rank parity-check matrix, the lower-bound on the density is of [4] showed that non-systematic irregular-repeat-accumulate (NSIRA) codes could achieve rates arbitrarily close to the channel-capacity of a BISOM channel with bounded complexity. The rates close to channel-capacity were achieved by randomly puncturing the information bits of the NSIRA codes indepedently with a probability that depended on the gap to capacity.…”
Section: Introductionmentioning
confidence: 99%